2022
DOI: 10.1002/sd.2380
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of the inequality in CO2 emissions per capita between developing countries and their implications for environmental policy

Abstract: We analyze the differences in CO 2 emissions from fuel combustion per capita between developing countries and how these are influenced by a series of affluence, structural, demographic, and climatic variables. First, a regression analysis provides new evidence on the determinants of CO 2 emissions in developing countries. We find an N-shaped relationship with GDP per capita and a negative impact of the agriculture share and average daily minimum temperatures, while urbanization and the share of potentially act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…From the perspective of PCE, Inc1 has higher PCE emissions compared to Inc2. This conclusion is basically consistent with the research viewpoint of many scholars (Padilla Rosa & Jadotte, 2023;Wiedenhofer et al, 2017), that is, wealthy households tend to use their increasing income for more goods and services, which leads to more PCE.…”
Section: Analysis Of Income Group Differencessupporting
confidence: 89%
“…From the perspective of PCE, Inc1 has higher PCE emissions compared to Inc2. This conclusion is basically consistent with the research viewpoint of many scholars (Padilla Rosa & Jadotte, 2023;Wiedenhofer et al, 2017), that is, wealthy households tend to use their increasing income for more goods and services, which leads to more PCE.…”
Section: Analysis Of Income Group Differencessupporting
confidence: 89%
“…However, urbanization had a negative effect on environmental sustainability in these countries. Padilla Rosa and Jadotte (2023) observed similar findings.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Regarding the sixth independent variable, CO 2 per capita, the global average (according to statistical data [40]) over the last 15 years is about 6.35 tones, which is 39% of the average of our database. A number of scientific studies have shown that high-income regions tend to have higher carbon dioxide emissions than countries in the upper-middle and lower-middle income brackets [41][42][43]. In terms of the food prices index, historical data from the FAO [44] shows that the world average is 106.5 points over the period 2007-2021, while our database shows that the average for Latin America and the Caribbean is 3 points below the average.…”
Section: Data Source and Data Descriptionmentioning
confidence: 77%